The way of the monk : how to find purpose, balance, and lasting happiness - Gaur Gopal Das, 1971- (2020)
"In The Way of the Monk, Gopal Das presents a guide to navigating some of the contemporary world's most fundamental questions. How can we achieve peace when the world is so full of noise and conflict? How do we learn to let go of attachment when consumer culture constantly tells us that we are unfulfilled? How can we embody love when our interactions with others are so fraught with old wounds and misunderstanding?"--
Keywords: Spiritual life -- International Society for Krishna Consciousness; Hare Krishnas; Spiritual life -- Hinduism